2002
DOI: 10.1590/s0074-02762002000800013
|View full text |Cite
|
Sign up to set email alerts
|

Larval dispersal and predation in experimental populations of Chrysomya albiceps and Cochliomyia macellaria (Diptera: Calliphoridae)

Abstract: In this study we investigated the larval dispersal associated with larval predation in experimental populations of Chrysomya albiceps and Cochliomyia macellaria. Frequency distribution of sampling units (G test)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…The dispersal of maggots away from carrion and from soil contaminated by carrion body fluids and by ammonium from the maggots can also accelerate the larval dispersal and have an impact on soil invertebrates and plants (Bornemissza 1957). Andrade et al (2002) used an acrylic channel to examine the influence of larval predation on larval dispersal in C. albiceps and C. macellaria. In two-species experiments, the number of C. albiceps larvae recovered was similar to the number initially released, whereas the number of C. macellaria larvae recovered was significantly smaller than that initially released.…”
Section: Recent Studies (2000-2004)mentioning
confidence: 99%
“…The dispersal of maggots away from carrion and from soil contaminated by carrion body fluids and by ammonium from the maggots can also accelerate the larval dispersal and have an impact on soil invertebrates and plants (Bornemissza 1957). Andrade et al (2002) used an acrylic channel to examine the influence of larval predation on larval dispersal in C. albiceps and C. macellaria. In two-species experiments, the number of C. albiceps larvae recovered was similar to the number initially released, whereas the number of C. macellaria larvae recovered was significantly smaller than that initially released.…”
Section: Recent Studies (2000-2004)mentioning
confidence: 99%
“…However, in the absence of C. macellaria, C. albiceps attacks C. putoria more often than C. megacephala (Faria & Godoy 2001). Attacks occur more often within the carcass, but may also occur outside, during larval dispersal (Andrade et al 2002, Gomes & Von Zuben 2005. Grassberger et al (2003) reported that the mortality rate of Lucilia sericata Meigen caused by predation from C. albiceps ranged from 57.6% to 99%, indicating a high susceptibility of L. sericata to attack by C. albiceps.…”
mentioning
confidence: 99%
“…Em experimentos de dispersão com espécies da família Calliphoridae, o número de larvas que dispersam também diminuiu com o aumento da distância (Greenberg 1990, Godoy et al 1995, 1996, de Andrade et al 2002. Nas maiores distâncias, compreendidas entre 40,1 cm e 50 cm, foram encontrados apenas 29 indivíduos, sendo que somente um atingiu a distância máxima possível durante o processo de dispersão (50 cm).…”
Section: Resultsunclassified